A multilevel job demands–resources model of work engagement: Antecedents, consequences, and boundary conditions. Issue 5 (20th October 2018) - Chen, Shu-Ling; Shih, Chih-Ting; Chi, Nai-Wen
ABSTRACT: Grounded on the Job Demands–Resources model, the present study conducted 2 studies to test a multilevel model of work engagement. Using data from 606 leader–employee pairs taken from 40 gas stations of a petroleum company, and a 3-wave data from 145 service teams and 542 leader–employee pairs from a variety of service organizations, convergent evidence suggested that (a) the unit leaders' autonomy-support climate and psychological capital lead to service performance through work engagement and (b) psychological capital could attenuate the positive effect of unit leaders'autonomy-support climate on work engagement. In addition, the unit leaders' autonomy-support climate acts as a job resource for boosting work engagement when both workloads and emotional demands or job insecurity are high.